Restoration of Belt Pulleys (Eurasian Scientific Herald, 2023)
This article describes the main work performed on the restoration and repair of emerging malfunctions of belt drive pulleys. Pulleys are the main parts of belt drives. Pulleys are used for the purpose of converting and transmitting torque over long distances